2018
DOI: 10.1002/cssc.201702451
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient Utilization of Zirconium Ions to Improve the Structure and Surface properties of Nickel‐Rich Cathode Materials for Lithium‐Ion Batteries

Abstract: We doped Zr ions in the outer layer of Ni Co Mn (OH) by coprecipitation. The distribution of Zr in the final cathode materials showed a gradient distribution because of ion migration during the thermal treatment. The doped layer was confirmed by using various analysis methods (energy-dispersive X-ray spectroscopy, XRD, X-ray photoelectron spectroscopy, and TEM), which implies that Zr can not only occupy both the transition metal slabs and Li slabs but also form a Li ZrO layer on the surface as a highly ion-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 51 publications
2
88
0
Order By: Relevance
“…[1][2][3] Rechargeable batteries, as one type of electrical energy storaged evice, can be applied not only for small devicess uch as laptopsa nd smartphones, but also for larges ystems, such as national electric grids, and spacecrafta nd transportation applications,s uch as electric vehicles (EVs). [1][2][3] Rechargeable batteries, as one type of electrical energy storaged evice, can be applied not only for small devicess uch as laptopsa nd smartphones, but also for larges ystems, such as national electric grids, and spacecrafta nd transportation applications,s uch as electric vehicles (EVs).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Rechargeable batteries, as one type of electrical energy storaged evice, can be applied not only for small devicess uch as laptopsa nd smartphones, but also for larges ystems, such as national electric grids, and spacecrafta nd transportation applications,s uch as electric vehicles (EVs). [1][2][3] Rechargeable batteries, as one type of electrical energy storaged evice, can be applied not only for small devicess uch as laptopsa nd smartphones, but also for larges ystems, such as national electric grids, and spacecrafta nd transportation applications,s uch as electric vehicles (EVs).…”
Section: Introductionmentioning
confidence: 99%
“…The obvious separations between the neighboring peaks of (006)/(102) and (108)/(110) show that all the samples have a characteristic highly crystallized layered structure. [28] For the modified samples, it can be observed that the position of (003) peak shifts to a lower angle, which means the expansion of the c axis. The full spectrum fitting with GSAS has been performed to gain the quantitative data of the lattice parameters.…”
Section: Resultsmentioning
confidence: 94%
“…Observed Bragg diffraction peaks could be indexed to a well‐defined α‐NaFeO 2 ‐type layered structure (R‐3m space group). The obvious separations between the neighboring peaks of (006)/(102) and (108)/(110) show that all the samples have a characteristic highly crystallized layered structure . For the modified samples, it can be observed that the position of (003) peak shifts to a lower angle, which means the expansion of the c axis.…”
Section: Resultsmentioning
confidence: 95%
“…To gain am ore accurate understanding of the doping of Yb ions, Rietveld refinement was performed. [13] The pristine Yb00d id not contain Yb ions, whereas the doped Yb03 displayed Yb ions at Ms ites with an occupancy of 0.27 %. The wRp obtained by the X-ray powder diffraction is about 10%, which is mainly attributed to the influence of the background height.…”
Section: Resultsmentioning
confidence: 99%